PROFIL PENGGUNAAN OBAT RASIONAL DI PUSKESMAS XY TAHUN 2023 - rahayu, sri (Jurnal Komunitas Farmasi Nasional, 2024)
Rational Drug Use (RDU) is a health service that strives to ensure the safety, effectiveness and cost-effectiveness of therapy in the community. We believe that the success of POR at the Community Health Centre can be measured by the percentage of antibiotic use (AB) for non-pneumonia, which has been reduced to 20%, the percentage of antibiotics in non-specific diarrhoea, which has been reduced to 8%, the percentage of injections in myalgia, which has been reduced to 1%, and the average number of drug items per prescription, which has been reduced to 2.6 items. The objective of this study was to gain a better understanding of the profile of rational drug use at the XY Community Health Centre in 2023. This research is a type of descriptive study, with data collection based on data contained in patient prescriptions. The data collection technique used was purposive sampling, which yielded a sample of 201. The results indicated that the percentage of antibiotic use in ISPA non-pneumonia cases in January was 17.64%, in February 50%, in March 36.84%, in April 25%, in May 28.12%, in June 19.04%, in July 21.15%, in August 43.63%, In September, the percentage of antibiotic use was 13.43%, in October it was 34.78%, in November it was 38.29%, in December it was 28.84%, and while the percentage of antibiotic use in non-specific diarrhoea in January was 0%, in February it was 5.88%, in March it was 7.69%, in April it was 0%, in May it was 0%, in June it was 10.63%. .63%), July (0%), August (11.76%), September (3.84%), October (36%), November (8.69%), December (0%), The average percentage of antibiotic use in ISPA non-pneumonia was 29.73%, while for non-specific diarrhoea was 7.04%. It can be surmised that, with regard to the profile of rational drug use for ISPA non-pneumonia at the XY Community Health Centre, the monthly average still falls short of WHO standards. Conversely, the profile of rational drug use for non-specific diarrhoea for the monthly average has met WHO standards.